Electricity Restructuring in China: The Elusive Quest for Competition - Russell Pittman; Vanessa Yanhua Zhang (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
The continuation of China's remarkable economic growth will depend on continued increases in electricity supply. China has commenced a program of electricity sector restructuring, with the announced aim of relying on markets and competition to provide incentives for attracting private investment and encouraging efficiency. However, a close examination of the generation markets being created suggests that truly free wholesale prices are likely to be both high and volatile. This may be the reason that these prices have not yet been freed – and it may not bode well for true market liberalization in the future.
Keywords: L94; O13; P28; Q48; 330; Electricity Restructuring; Competition; China